Development and validation of the Investigator® Quantiplex Pro Kit for qPCR-based examination of the quantity and quality of human DNA in forensic samples. (December 2017) - Vraneš, Miroslav; Scherer, Mario; Elliott, Keith
Abstract: We developed and validated the Investigator Quantiplex Pro Kit which quantifies human and male DNA in a sample using quantitative real-time PCR. An internal PCR control (IPC) is incorporated into the kit to reliably and consistently identify PCR inhibitors that may interfere with downstream processes, such as STR PCR. In addition, the effect of DNA degradation on downstream STR analysis can be accurately assessed. The kit works with any human ID workflow, regardless of upstream sample prep or downstream STR kit, and has been designed to complement the Quality Sensor found in several of QIAGEŃs Investigator STR PCR assays (Investigator ESSplex SE QS, Investigator 24plex QS and Investigator 24plex GO!), enabling an unparalleled level of workflow optimization.